Photobiomodulation and the oral-gut microbiome axis: therapeutic potential and challenges - Hakimiha, Neda; Jahani Sherafat, Somayeh; Laakso, E-Liisa; Fekrazad, Reza (Frontiers in Medicine, 2025)
This Perspective article explores the challenges associated with the direct application of photobiomodulation (PBM) to the gut and presents a novel hypothesis for indirect gut health modulation through oral microbiome alteration. Given the difficulties in delivering PBM effectively to deep gastrointestinal tissues, an alternative approach involves targeting the oral microbiome, which has a demonstrated relationship with the gut microbiome. Research indicates that PBM applied to the oral cavity could selectively alter microbial composition. This alteration may, via the oral-gut microbiome axis, indirectly impact gut health. This hypothesis, supported by preliminary studies, suggests that oral PBM could offer a promising non-invasive strategy for managing gut-related disorders. Furthermore, there may be a link between the oral microbiome and brain diseases. Given the proximity to the brain, PBM-induced changes in the oral microbiota could indirectly help prevent neurological disorders. However, further investigation is necessary to comprehensively elucidate the underlying mechanisms and therapeutic implications of this approach.